ASSETS PRODUCTIVITY AND COMMUNITY HEALTH ACTIVITIES DISCLOSURES ON MANUFACTURING COMPANIES - Adam, Helmy; Sari, Kristina Mevita (JRAK: Journal of Accounting Research and Computerized Accounting, 2020)
This study aims to describe and analyze various public health activities that are revealed in the annual publications of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2017-2018. Base on 93 companies that were observed, 84 companies (95.2%) had disclosed their public health activities, while 9 companies (4.8%) did not make any consecutive disclosures for 2 (two) years. The results of this study also indicate that, disclosure of aspects of public health was influenced by Return on Assets (ROA) which means that public health programs are influenced by the productivity of company assets in generating profits.